PERFORMANCE OF YANKASA RAMS FED CORN COB BASAL DIET SUPPLEMENTED WITH MIXTURE OF SUN-DRIED BROILER LITTER AND DIFFERENT ENERGY SUPPLEMENTS - Zagi, S. P.; Mahmud, M. (FUDMA JOURNAL OF SCIENCES, 2022)
A total of sixteen (16) Yankasa rams of about 10-12 months of age and having an average weight of 24 kg were used in an 84-day trial to investigate the nutrient utilization and digestibility of Yankasa rams fed grounded corn cob as basal diet supplemented with sun-dried broiler litter (SDPL) and different energy concentrate mixture. The rams were randomly assigned into four (4) treatments with four (4) replicates per treatment in a completely randomized design (CRD). Four experimental diets were formulated and designated as: T1 (Corn cob + 150g SDPL + 150g MB), T2 (Corn cob + 150g SDPL + 150g RB), T3 (Corn cob + 150g SDPL + 150g MO), and T4 (Corn cob + 150g SDPL + 150g WO) and used to feed the Yankasa rams. The result of the performance of the rams showed that basal feed intake (35360.00-37735.00g; P<0.05), supplement feed intake (25077.50-25200.00g; P<0.05), total feed intake 60437.50-62935.00g; P<0.05), daily feed intake (719.49-749.23g; P<0.05), feed conversion ratio (7.74-9.11; P<0.05) and water intake 199.93-206.93L; P<0.05) were significantly affected across dietary treatments. On the daily weight of the rams, final weight (30500.00-32250.00g; P<0.05), weight gain (6750.00-8000.00g; P<0.05) and daily weight gain (80.36-95.24g; P<0.05) was significantly (P<0.05) while initial weight did not differ significantly. Poultry litter inclusion in ruminant diets could enhance the active utilization of fibrous feed materials and crop residues used in formulation. It could also possibly have role in supplying active microbial network that could enhance digestibility and degradability of rumen dietary fractions.